"An Immaculate Keeper of My Social Media Feed": Social Media Usage in Body Justice Communities During the COVID-19 Pandemic. (February 2022) - Greene, Amanda K.; Maloul, Elana; Kelly, Devin A.; Norling, Hannah N.; Brownstone, Lisa M.
This article examines how individuals proximate to online body justice communities utilized and experienced social media during COVID-19. The majority of research during the pandemic has been quantitative and survey-based; it has also tended to center (dis)information spread or mental health concerns. Our qualitative interviews with 44 individuals offer nuanced insights into what social media meant to people during quarantine, how they used it, and how they reflected on their experience of it. Five major themes emerged through reflexive, thematic analysis of the interview data: changed temporal rhythms, influx of toxic content, resource building, additive and subtractive actions, and algorithmic awareness. Some participants described social media as an increasingly harmful influence in their lives during the pandemic due to compulsive usage and exposure to "toxic content" like misinformation, weight stigma, and homophobia. At the same time, participants noted how social media positively enabled social connection, education, and activation around social justice. Across both of these extremes, many elaborated on the intensive, self-reflective labor of cultivating their accounts so that they mirrored their identities and the kinds of experiences they wanted to have online while preventing the infiltration of unwanted content. In addition to offering new insights into social media usage in body justice communities during COVID-19, our data suggest alternative ways of understanding how individuals manage their experience of social media, curate their social media feeds through additive and subtractive actions, and frequently reflect on how their choices interact with platform algorithms.